Two female perspectives on the slave family as described in Harriet Jacobs' "Incidents in the Life of a Slave Girl" and Mattie Griffith's "Autobiography of a Female Slave". - Lystar, Kimberley J. (University of Ottawa (Canada), 1996)
This thesis will explore an issue in the history of American slavery: the importance of the slave family to individual female slaves. The slave families examined in this thesis do not consist exclusively of blood relations. They also include groups of individuals who came together and depended on and loved one another as much as blood relations. These bonds of affection also constituted family. In the main part of the thesis two sources will be examined in great detail: Harriet Jacobs' Incidents in the Life of a Slave Girl, published in 1861; and Mattie Griffith's Autobiography of a Female Slave, published in 1856. The main issue to be discussed is how these two women described the interaction of members of slave families. Jacobs was a fugitive slave living in the North when she wrote her slave narrative, Incidents in the Life of a Slave Girl in the 1850s. Griffith, on the other hand, was a white women who wrote a slave novel entitled Autobiography of a Female Slave in 1856. (Abstract shortened by UMI.)
Keywords: History, Black.